Natural Killer Cells for Immunotherapy – Advantages of the NK-92 Cell Line over Blood NK Cells - Klingemann, Hans; Boissel, Laurent; Toneguzzo, Frances (Frontiers in Immunology, 2016)
Natural killer cells are potent cytotoxic effector cells for cancer therapy and potentially for severe viral infections. However, there are technical challenges to obtain sufficient numbers of functionally active NK cells form a patient’s blood since they represent only 10% of the lymphocytes. Especially, cancer patients are known to have dysfunctional NK cells. The alternative is to obtain cells from a healthy donor, which requires depletion of the allogeneic T-cells. Establishing cell lines from donor blood NK cells have not been successful, in contrast to blood NK cells obtained from patients with a clonal NK cell lymphoma. Those cells can be expanded in culture in the presence of IL-2. However, except for the NK-92 cell line none of the other six known cell lines has consistent and reproducibly high anti-tumor cytotoxicity, nor can they be easily genetically manipulated to recognize specific tumor antigens or to augment monoclonal antibody activity through ADCC. NK-92 is also the only cell line product that has been widely given to patients with advanced cancer with demonstrated efficiency and minimal side effects.